Polycrystalline cubic boron nitride body
Patent Information
- Application Number
- JP2023572621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-27
- Filing Date
- 2022-05-25
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-05-25
AI Technical Summary
Current tooling solutions for machining high-temperature nickel-based or cobalt-based superalloys (HRSA) are limited by low cutting speeds and high wear rates, leading to poor surface quality and reduced tool life due to crater wear, escape wear, notching, cracking, chipping, and plastic deformation.
A polycrystalline cubic boron nitride (PCBN) sintered body comprising 40-85% cubic boron nitride particles and 15-60% binder phase, with a composition including zirconium oxide, alumina, and metal nitrides such as aluminum nitride, vanadium nitride, niobium nitride, or hafnium nitride, enhancing wear resistance and tool life.
The PCBN body demonstrates improved escape wear resistance and notch wear resistance, leading to longer tool life and enhanced machining performance compared to conventional PCBN materials with TiC or TiCN binders.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to polycrystalline cubic boron nitride (PCBN) bodies, methods for making said polycrystalline cubic boron nitride (PCBN) bodies, and uses thereof. [Background technology]
[0002] Current tooling solutions for difficult-to-machine materials, such as heat-resistant nickel-based or cobalt-based superalloys (HRSA), are typically limited to the use of coated cemented carbide tools operating at relatively low cutting speeds, which is currently common practice in the aerospace manufacturing industry.
[0003] The main wear modes observed when machining HRSA alloys are crater wear, flank / nose wear, notching, cracking, chipping, plastic deformation, and catastrophic fracture. Cratering often belongs to the diffusion or dissolution wear mechanism, where smooth wear surfaces are observed. In addition, wear is accompanied by the progression of flank wear due to the softening of the tool material at high cutting temperatures. The flank of the cutting tool is exposed to the contact movement of the workpiece and flank wear, which leads to poor surface quality of the workpiece, inaccuracies in the cutting process, and increased friction as the cutting progresses. Polycrystalline cubic boron nitride (PCBN) cutting tools are highly valued when machining HRSA alloys, due to their ability to maintain high hardness at high temperatures.
[0004] With the increasing demand for increased productivity, for example by increasing cutting speeds or having high metal removal rates, alternative solutions to coated cemented carbides have emerged in aero-engine manufacturing and can be used in semi-finishing applications for high speed machining of HRSA alloys. An example of an alternative solution currently in use is PCBN cutting tools with titanium carbide (TiC) or titanium carbonitride (TiCN) based binders.
[0005] PCBN materials still have a high cost compared to cemented carbide materials, and to be cost-effective they need to demonstrate even higher productivity than traditional PCBN solutions with TiC or TiCN as binders.
[0006] Patent application WO2011098556A1 discloses examples of PCBN materials with conventional binder phases including TiC or TiCN. Deviating from conventional PCBN compositions, patent application EP3239116A1 shows PCBN bodies having 40 and 85 volume percent (vol%) cBN and 15 and 60 vol% binder phase. The binder phase is primarily comprised of aluminum (Al) compounds such as Al2O3, AlN, and the like, with additives being zirconium oxide (Zr) compounds such as zirconium oxide (ZrO), and zirconium dioxide (ZrO2) in an amount up to 10 vol% of the total cubic boron nitride body.
[0007] To meet the above demands, there is a need for new PCBN materials that can be used in cutting tool bodies and have advanced properties that improve tool life during machining operations. Better flank and / or notch wear resistance can result in longer tool life for some machining applications and operations. Summary of the Invention
[0008] It is an object of the present invention to provide a sintered PCBN body having improved performance in machining operations.
[0009] This object is achieved by a PCBN body as defined in claim 1 and a method as defined in claim 14.
[0010] The present disclosure provides a polycrystalline cubic boron nitride (PCBN) sintered body comprising between 40 and 85 volume % of cubic boron nitride (cBN) particles and between 15 and 60 volume % of a binder phase, the binder phase comprising at least one metal oxide and at least one metal nitride, the at least one metal oxide comprising between 20 and 100 volume % of zirconium oxide (ZrO2) and up to 80 volume % of alumina (Al2O3), calculated as a volume percentage of the total metal oxide content of the binder, the at least one metal nitride comprising aluminum nitride (AlN) and at least one metal nitride selected from the group consisting of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN), the content of the metal nitride being at least 10 volume % of the binder phase. This results in a PCBN body with improved performance in machining operations.
[0011] The present disclosure also provides a polycrystalline cubic boron nitride (PCBN) sintered body comprising between 40 and 85 volume % cubic boron nitride (cBN) particles and between 15 and 60 volume % of a binder phase, said binder phase comprising at least one metal oxide and at least one metal nitride, said at least one metal oxide comprising between 20 and 100 volume % zirconium oxide (ZrO2) and up to 80 volume % alumina (Al2O3), calculated as a volume percentage of the total metal oxide content of the binder, said at least one metal nitride being selected from the group consisting of aluminum nitride (AlN), vanadium nitride (VN), niobium nitride, and the like. The present invention provides a polycrystalline cubic boron nitride (PCBN) sintered body comprising at least one metal nitride selected from the group consisting of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN), wherein the content of the metal nitride selected from at least one of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN) constitutes at least 10% by volume of the total binder phase, and the at least one metal oxide constitutes at least 10% by volume, preferably, for example, at least 20% by volume, or at least 30% by volume, or at least 40% by volume, or at least 50% by volume, or at least 60% by volume of the total binder phase.
[0012] According to one embodiment, the content of AlN in the polycrystalline cubic boron nitride (PCBN) sintered body ranges from 1 to 10 vol. %, such as 1 to 7 vol. %, such as 2 to 6 vol. % or 3 to 5 vol. % of the total binder phase. According to some aspects, the binder phase of the PCBN body further comprises at least one metal oxynitride which is a reaction product of one of the at least one metal oxides and one of the at least one metal nitrides. In other words, when the binder phase comprises at least one metal oxynitride, the at least one metal oxynitride is a reaction product of a metal oxide selected from the group consisting of ZrO2 and Al2O3 and a metal nitride selected from the group consisting of VN, NbN and HfN. Tests have shown that the average tool life of PCBN bodies having a binder phase according to the composition disclosed above is improved compared to prior art solutions using other types of binder phase compositions. When the binder phase of the PCBN body has a composition according to the compositions disclosed above, higher flank wear resistance is obtained during machining than prior art solutions, as well as higher notch wear resistance, when the same cutting parameters are used.
[0013] According to some embodiments, the PCBN body comprises between 50 and 75% by volume cBN particles, preferably between 60 and 75% by volume cBN particles, and even more preferably between 60 and 70% by volume cBN particles.
[0014] According to some embodiments, the PCBN body comprises between 25 and 50% by volume of binder phase, preferably between 25 and 40% by volume of binder phase, and even more preferably between 30 and 40% by volume.
[0015] According to some embodiments, the content of cBN particles and binder phase in the PCBN body is up to 100% by volume of the PCBN body.
[0016] According to some embodiments, the content of metal oxides, metal nitrides and metal oxynitrides in the binder phase is up to 100% by volume of the binder phase.
[0017] According to some embodiments, the binder phase comprises at least one oxynitride selected from the group consisting of zirconium oxynitride (Zr(O,N)), zirconium vanadium oxynitride ((Zr,V)ON), zirconium niobium oxynitride ((Zr,Nb)ON), and zirconium hafnium oxynitride ((Zr,Hf)ON).
[0018] According to some embodiments, the binder phase comprises at least one oxynitride selected from the group consisting of aluminum oxynitride (Al(O,N)), aluminum vanadium oxynitride ((Al,V)ON), aluminum niobium oxynitride ((Al,Nb)ON), and aluminum hafnium oxynitride ((Al,Hf)ON).
[0019] According to some embodiments, the binder phase consists of ZrO2, Al2O3, AlN, and at least one metal nitride selected from the group consisting of VN, NbN, and HfN.
[0020] According to some embodiments, the metal nitrides selected from the group consisting of VN, NbN and HfN constitute up to 60% by volume of the total binder, such as up to 50% by volume of the total binder phase, such as up to 40% by volume or up to 30% by volume or up to 20% by volume of the total binder phase. Having up to 60% by volume or up to 50% by volume or up to 40% by volume or up to 30% by volume or up to 20% by volume of the total binder phase that are metal nitrides from the group consisting of VN, NbN and HfN improves the mechanical properties of the material and chipping resistance of the cutting edge compared to binders that include only metal oxide phases.
[0021] According to some embodiments, the metal nitrides selected from the group consisting of VN, NbN and HfN comprise between 10 and 50 volume percent of the total binder phase. Having between 10 and 50 volume percent of the total binder phase that is a metal nitride from the group consisting of VN, NbN and HfN improves the mechanical properties of the material and chipping resistance of the cutting edge compared to binders that contain only metal oxide phases.
[0022] According to one embodiment, metal nitrides selected from the group consisting of VN, NbN and HfN constitute at least 20% by volume, or at least 30% by volume, or at least 40% by volume of the total binder phase.
[0023] According to one embodiment, the at least one metal oxide and aluminum nitride together constitute up to 90 vol.%, or up to 80 vol.%, or up to 70 vol.%, or up to 60 vol.%, or up to 50 vol.%, or up to 40 vol.%, or up to 30 vol.%, or up to 20 vol.% of the total binder phase, the aluminum nitride content being as further specified herein.
[0024] According to some embodiments, the binder phase is comprised of ZrO2, Al2O3, and at least one metal nitride selected from the group consisting of AlN, VN, NbN, and HfN, and at least one oxynitride selected from the group consisting of Zr(O,N), (Zr,V)ON, (Zr,Nb)ON, (Zr,Hf)ON, Al(O,N), (Al,V)ON, (Al,Nb)ON, and (Al,Hf)ON. Testing has shown that the average tool life of PCBN bodies containing a binder phase consisting of ZrO2, Al2O3, and at least one metal nitride selected from the group consisting of AlN, VN, NbN and HfN, and at least one oxynitride selected from the group consisting of Zr(O,N), (Zr,V)ON, (Zr,Nb)ON, (Zr,Hf)ON, Al(O,N), (Al,V)ON, (Al,Nb)ON and (Al,Hf)ON is increased compared to prior art solutions using other types of binder phase compositions.
[0025] According to some embodiments, the oxynitrides and metal nitrides are between 10 and 50% by volume of the total binder phase of the PCBN body. Preferably, the oxynitrides and metal nitrides are between 25 and 50% by volume of the total binder phase of the PCBN body.
[0026] According to some embodiments, ZrO2 is between 20 and 90 volume % of the total content of metal oxides in the binder phase. Preferably, ZrO2 is between 50 and 90 volume % of the total content of metal oxides in the binder phase, and even more preferably, ZrO2 is between 70 and 90 volume % of the total content of metal oxides in the binder phase.
[0027] According to some embodiments, Al2O3 is between 5 and 25 volume % of the total binder phase. Preferably, Al2O3 is between 5 and 15 volume % of the total binder phase. According to one embodiment, a further constituent may be included in the binder phase, such as TiC or other conventionally used constituents. However, the binder phase preferably consists of metal oxides and metal nitrides as further specified herein.
[0028] According to some embodiments, the PCBN body is backed by a cemented carbide substrate.
[0029] According to some embodiments, the PCBN body is coated with a PVD coating or a CVD coating having a thickness between 0.8 μm and 15 μm.
[0030] According to some embodiments, the PCBN body is a single (Ti 1―x Al x )N z (where 0.1 < x < 0.4, 0.6 < z < 1.2) layer of a first (Ti,Al)-based nitride subcoating, and a (Ti 1―x1―y1 Al x1 Cr y1 )N z1 (where 0.5 < x1 < 0.75, 0.05 < y1 < 0.2, 0.6 < z1 < 1.2) layer, and is coated with a PVD coating including a second (Ti,Al)-based nitride subcoating having a laminated structure. Preferably, the thickness of the first (Ti,Al)-based nitride subcoating is between 0.1 μm and 2 μm. The second (Ti,Al)-based nitride subcoating having a laminated structure is an alternating body of layer A and layer B: A / B / A / B / A / B / ..., (where layer A is (Ti 1―x Al x )Nz and 0.1 < x < 0.4, 0.6 < z < 1.2, and layer B is (Ti 1―x1―y1 Al x1 Cr y1 )N z1 and 0.5 < x1 < 0.75, 0.05 < y1 < 0.2, 0.6 < z1 < 1.2). Preferably, the second (Ti,Al)-based nitride subcoating has a laminated structure with a thickness between 0.5 μm and 10 μm, and the A and B layers of the laminated structure have an average individual layer thickness between 1 nm and 100 nm, preferably between 5 nm and 50 nm, and most preferably between 5 nm and 30 nm.
[0031] According to some embodiments, in the above PCBN body, layer A is (Ti 1―x Al x Me1 p )Na, where 0.3 < x < 0.95, preferably 0.45 < x < 0.75, 0.90 < a < 1.10, preferably 0.96 < a < 1.04, 0 ≤ p < 0.15, Me1 is one or more of Zr, Y, V, Nb, Mo, and W, and layer B is (Ti 1―y―z Si y Me2 z )N b where 0.05 < y < 0.25, preferably 0.05 < y < 0.18, 0 ≤ z < 0.4, 0.9 < b < 1.1, preferably 0.96 < b < 1.04, Me2 is one or more of Y, V, Nb, Mo, W, and Al, and is columnar and coated with a PVD coating including a polycrystalline nanolaminated structure of an alternating body of layer A and layer B. The thickness of the above nanolaminated structure is between 0.5 μm and 10 μm, preferably between 0.5 μm and 5 μm, the average column width is between 20 nm and 1000 nm, and the average individual thickness of layer A and layer B is between 1 nm and 50 nm.
[0032] According to some embodiments, the above PCBN body is a cutting tool or a cutting tip of a cutting tool. The above cutting tool is used for machining by chip removal, such as in turning, milling, or drilling operations. Examples of cutting tools are indexable cutting inserts, solid drills, and end mills.
[0033] The present disclosure provides a method for producing a PCBN body according to any of the above aspects, comprising the steps of: (a) providing cubic boron nitride (cBN) powder having an average particle size between 0.5 μm and 15 μm; (b) providing a binder composition comprising ZrO2 or a mixture of ZrO2 and Al2O3, at least one metal nitride selected from the group consisting of VN, NbN and HfN constituting at least 10 volume percent of the binder mixture, and metallic aluminum; (c) combining the binder composition with cBN powder to form a powder mixture; (d) grinding the powder mixture; (e) forming a green body of the powder mixture; (f) heat treating the green body at a temperature above 600° C. under reduced pressure to ensure sufficient degassing and removal of absorbed species; (g) sintering the green body at a temperature of at least 1200° C. and at a pressure of at least 4 GPa to form a solid PCBN sintered compact therefrom; and forming a PCBN body therefrom. The present invention provides a method comprising:
[0034] According to one embodiment, metallic aluminum is added in an amount of 1 to 10% or 1 to 5% by volume of the total amount of added components.
[0035] According to some embodiments, the heat treating step of the green body is carried out at a temperature less than 1100°C.
[0036] According to some embodiments, the sintering of the green body is carried out at a temperature below 2000°C.
[0037] According to some embodiments, the produced solid PCBN sintered compact is then cut into pieces using electrical discharge machining (EDM) or a laser.
[0038] The present disclosure provides for the use of a PCBN body according to any of the above embodiments for machining a nickel-based superalloy and / or a cobalt-based superalloy.
[0039] The invention is explained in more detail hereinafter by the description of various embodiments of the invention and with reference to the accompanying drawings. [Brief description of the drawings]
[0040] [Figure 1] FIG. 1 illustrates an example of a solid PCBN body. [Diagram 2] FIG. 13 shows another example of a solid PCBN body using a carbide substrate brazed to a cemented carbide insert carrier. [Diagram 3] FIG. 13 shows an optical microscope image of flank wear on a PCBN body according to an embodiment of the present invention. [Figure 4] FIG. 13 shows an optical microscope image of flank wear on a first comparative PCBN body. [Diagram 5] FIG. 13 shows an optical microscope image of flank wear on a second comparative PCBN body. [Figure 6] FIG. 13 shows an optical microscope image of notch wear on a PCBN body according to an embodiment of the present invention. [Figure 7] FIG. 13 shows an optical microscope image of notch wear on a first comparative PCBN body. [Figure 8] FIG. 13 shows an optical microscope image of notch wear on a second comparative PCBN body. [Figure 9] 1 shows a block diagram of an example method for manufacturing a PCBN body. [Figure 10] FIG. 1 shows an SEM image and XEDS mapping of various elements of a PCBN body according to an embodiment of the present invention. [Figure 11] FIG. 2 shows an X-ray θ-2θ diffractogram of a PCBN body according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] Aspects of the present disclosure are described more fully hereinafter with reference to the accompanying drawings. However, the devices and methods disclosed herein may be embodied in many different forms and should not be construed as limited to the aspects set forth herein. Like numbering in the drawings refers to like elements throughout.
[0042] The terminology used in this disclosure is for the purpose of describing certain aspects of the disclosure only and is not intended to limit the invention. As used herein, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise.
[0043] The term "cutting tool", as used herein, is intended to denote a cutting tool suitable for metal cutting by chip removal, such as turning, milling or drilling. Examples of cutting tools are indexable cutting inserts, solid drills and end mills.
[0044] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0045] Common to cutting tool inserts is that they may be a solid body or a body including a base body on which additional material is disposed either on the cutting edge on the rake face, a so-called chip-attached body, or such that the cutting tool insert covers the entire rake face, a so-called full-face body.
[0046] FIG. 1 shows an example of a PCBN body 1. The PCBN body of FIG. 1 is a solid body. The solid PCBN body 1 in FIG. 1 may be a cutting tool insert by itself or may be cut into pieces for use as cutting tips of cutting tool inserts. FIG. 2 shows an example of a cutting tool insert 3 including a substrate 4 and a cutting tip in the form of a PCBN body 2 according to the present disclosure. The PCBN body 2 is integrally bonded to the substrate 4, which may be made of, for example, cemented carbide.
[0047] The present disclosure provides a PCBN sintered body 1, 2 comprising between 40 and 85 volume % cubic boron nitride (cBN) particles and between 15 and 60 volume % of a binder phase, the binder phase comprising at least one metal oxide and at least one metal nitride. The at least one metal oxide comprises between 20 and 100 volume % zirconium oxide (ZrO2) and up to 80 volume % alumina (Al2O3), calculated as a volume percentage of the total metal oxide content of the binder. Furthermore, the at least one metal nitride comprises aluminum nitride (AlN) and at least one metal nitride selected from the group consisting of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN). The content of the metal nitride is at least 10 volume % of the binder phase.
[0048] The binder phase of the PCBN body 1 may, for example, include at least one metal oxynitride that is a reaction product of at least one metal oxide and at least one metal nitride.
[0049] The binder phase may, for example, comprise at least one oxynitride selected from the group consisting of zirconium oxynitride (Zr(O,N)), zirconium vanadium oxynitride ((Zr,V)ON), zirconium niobium oxynitride ((Zr,Nb)ON), and zirconium hafnium oxynitride ((Zr,Hf)ON).
[0050] Alternatively or additionally, the oxynitride may include at least one oxynitride selected from the group consisting of aluminum oxynitride (Al(O,N)), aluminum vanadium oxynitride ((Al,V)ON), aluminum niobium oxynitride ((Al,Nb)ON), and aluminum hafnium oxynitride ((Al,Hf)ON).
[0051] The content of oxynitrides and at least one metal nitride of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN) is for example between 10 and 50% by volume of the total binder phase.
[0052] FIG. 9 shows a block diagram of an example of a method for manufacturing the PCBN bodies 1 and 2. According to the above example method, the following steps are performed: (a) preparing a cubic boron nitride (cBN) powder having an average particle size between 0.5 μm and 15 μm; (b) providing ZrO2 or a mixture of ZrO2 and Al2O3, at least one metal nitride selected from the group consisting of VN, NbN and HfN, the metal nitride being at least 10% by volume of the binder mixture, and a metal aluminum binder composition; (c) combining the binder composition with cBN powder to form a powder mixture; (d) grinding the powder mixture; (e) forming a green body of the powder mixture; (f) heat treating the green body at a temperature above 600° C. under reduced pressure to ensure sufficient degassing and removal of absorbed species; (g) sintering the green body at a temperature of at least 1200° C. and at a pressure of at least 4 GPa to form a solid PCBN sintered compact therefrom to form a PCBN body (1, 2); will be implemented.
[0053] According to an alternative exemplary process, the following steps are performed to manufacture a PCBN body: - preparing cubic boron nitride (cBN) powder having an average particle size between 0.5 μm and 15 μm from hexagonal boron nitride (hBN) powder, which is carried out at high temperature and pressure according to standard practice; - providing a binder mixture of binder constituents comprising ZrO2 or a mixture of ZrO2 and Al2O3, at least one metal nitride selected from the group consisting of VN, NbN and HfN, said metal nitride being at least 10% by volume of said binder mixture, and metallic aluminum, - grinding said binder mixture to an average particle size of the binder constituent between 0.5 μm and 10 μm; - combining the ground binder mixture with cBN powder to form a powder mixture; - milling said powder mixture to reduce the average particle size and ensure accurate mixing and dispersion of the cBN phase in the binder mixture; - forming a green body of said powder mixture; - heat treating said green body at a temperature above 600°C under reduced pressure to ensure sufficient degassing and removal of absorbed species; - sintering the green body at a temperature of at least 1200°C and at a pressure of at least 4 GPa to form a solid PCBN sintered compact, and then forming a PCBN body.
[0054] The solid PCBN sintered compact is cut into pieces, for example by using EDM or a laser. The cut pieces forming the PCBN bodies 1, 2 may be brazed to a cemented carbide substrate 4 and formed into, for example, a cutting tool as seen in FIG.
[0055] According to an example embodiment, PCBN bodies 1 and 2 were produced according to the method described above, the PCBN bodies having about 60% by volume of cBN grains and a binder phase including ZrO2 (both cubic and tetragonal), Al2O3, AlN, VN and zirconium oxynitride (Zr(O,N)). FIG. 10 shows the XEDS mapping of various elements in the PCBN body, which shows how the cBN grains including B and N are present in the binder phase including O, N, Al, V and Zr. FIG. 11 shows the X-ray diffraction (XRD) intensities of cubic BN, ZrO2 (both cubic and tetragonal), Al2O3, AlN, VN and zirconium oxynitride (Zr(O,N)) in the PCBN body measured using Cu-Kα radiation and θ-2θ scan. The diffractometer used was a STOE STADI MP. For the analysis of the XRD patterns in FIG. 11, the following Crystal Impact Entry (CIE)-cards were used: Al2O3, CIE card: 96-100-0018 AlN, CIE card: 96-152-3096 BN, CIE-Card: 96-035-1365 (cubic crystal) VN, CIE-Card: 96-035-0768 ZrO2, CIE card: 95-050-1089 (tetragonal) ZrO2, CIE card: 96-900-7449 (cubic) Zr x (O,N) y , CIE-Card: 96-050-1172 EXAMPLES
[0056] Example 1 A PCBN cutting tool according to an embodiment of the present disclosure having a composition corresponding to Sample 1 in Table 1 was made according to the above alternative embodiment of the manufacturing method. A first comparative PCBN cutting tool having a conventional TiC-binder having a composition according to Sample 2 in Table 1, and a second comparative PCBN cutting tool having a conventional TiCN-binder having a composition according to Sample 3 in Table 1 were made under the same powder preparation and sintering conditions as Sample 1.
[0057] Cutting tools were manufactured with ISO RNGN090300 insert geometry. TIFF2024521758000002.tif53170 A PCBN cutting tool having the composition according to Samples 1-3 was used to perform longitudinal turning of Inconel 718 workpiece material supplied in an aged condition and having a hardness of HRC45.
[0058] The cutting data used were as follows: 1. Feed rate f = 0.10 mm / revolution, cutting speed v c =300m / min 2. Feed rate f = 0.10 mm / rev, cutting speed v c =350m / min On the other hand, the cutting depth was a, which corresponds to the high-speed finishing condition, in both cases. p = 0.3 mm. High pressure localized cooling (HPDC) was applied using an 8% oil-water emulsion as the coolant, and the coolant pressure was set at 90 bar on the rake and flank faces of the cutting tool.
[0059] cutting speed v c = 300 m / min for 3.2 min, and cutting speed v c The flank wear was measured after a helix length of 950 meters, which corresponds to a cutting time of 2.7 minutes at =350 m / min.
[0060] Flank wear was measured using an Olympus SZX7 optical microscope.
[0061] The flank wear measured at cutting speeds of 300 m / min and 350 m / min is shown in Table 2. TIFF2024521758000003.tif48170The SEM images in Figs. 3, 4 and 5 were taken at a cutting speed of 350 m / min, feed rate f = 0.1 mm / revolution and cutting depth a p The graph shows the flank wear of samples 1 to 3 at 0.3 mm after 2.7 minutes.
[0062] From the experimental results and observations regarding Example 1, it was concluded that PCBN cutting tools having a composition according to the present invention demonstrated greater than 50% improvement in performance compared to conventional TiC-bonds and TiCN-bonds.
[0063] Example 2 A lathe cutting of a curved profile with a radius of curvature R38.5 mm was carried out on an Inconel 718 workpiece material supplied in an aged state and having a hardness of HRC45. A PCBN cutting tool having the same composition as in Example 1, i.e., compositions according to Samples 1 to 3 in Table 1, was used.
[0064] Three different cases of cutting data were used: 1. Feed rate f = 0.10 mm / revolution, cutting speed v c =350m / min 2. Feed rate f = 0.08 mm / revolution, cutting speed v c =420m / min 3. Feed rate f = 0.10 mm / rev, cutting speed v c =420m / min On the other hand, the cutting depth was a, which corresponds to the high-speed finishing condition, in all three cases. p = 0.3 mm. High pressure localized cooling (HPDC) was applied using an 8% oil-water emulsion as the coolant, and the coolant pressure was set at 70 bar on the rake and flank faces of the cutting tool.
[0065] Cutting tools were manufactured with ISO RNGN090300 insert geometry.
[0066] The flank wear and notch wear were measured at time intervals of 0.89 minutes ± 0.11 minutes, and the performance test was stopped either when the maximum flank wear exceeded the standard of 250 μm or when the notch wear exceeded the standard of 1000 μm.
[0067] The PCBN cutting tool with TiC as the main binder phase, i.e., sample 2, was cut at a feed rate of f = 0.08 mm / rev and a cutting speed of v c = 420 m / min cutting conditions, critical notch wear developed at a high rate and failed due to edge breakage, so it is not included in Table 3 showing the tool wear for Example 2.
[0068] Flank wear and notch wear were measured using an Olympus SZX7 optical microscope.
[0069] Table 3 shows the flank wear measured at each cutting time interval when the flank wear or boundary wear parameter reached its limit criterion for the three different sets of cutting data used. TIFF2024521758000004.tif70170Table 4 shows the notch wear measured for the three different sets of cutting data used. TIFF2024521758000005.tif67170The SEM images in Figs. 6, 7 and 8 were taken at cutting speeds of v c = 350 m / min, feed rate f = 0.1 mm / revolution and cutting depth a p = 0.3 mm for each of Samples 1, 2 and 3. The results of the notch wear (μm) and cutting time (min) for the samples in Figures 6, 7 and 8 are also shown in the first column of Table 4. As can be seen from Table 4, Sample 1 had the longest cutting time at 7.50 / min, i.e. it cut twice as long as Sample 2 and had 33% longer time than Sample 3, and at the same time Sample 1 still had lower notch wear than either Sample 2 and 3.
[0070] From the experimental results and observations regarding Example 2, it was concluded that Sample 1, i.e., a PCBN cutting tool according to the present disclosure, provided greater than 110% improvement in performance by boundary wear criterion compared to conventional TiC-bonds and TiCN-bonds, while demonstrating greater than 31% improvement in performance by flank wear criterion.
[0071] The invention is not limited to the disclosed embodiments, but may be varied and modified within the scope of the following claims.
Claims
1. A polycrystalline cubic boron nitride (PCBN) sintered body (1, 2) comprising between 40% and 85% by volume of cubic boron nitride (cBN) particles and between 15% and 60% by volume of a binder phase, the binder phase comprising at least one metal oxide and at least one metal nitride, At least one metal oxide is zirconium oxide (ZrO 2 ) between 20 volume % and 100 volume %, and alumina (Al 2 O 3 % up to 80% by volume of aluminum nitride (AlN), the at least one metal nitride comprising 1% to 10% by volume of aluminum nitride (AlN) relative to the total binder phase, and at least one metal nitride selected from the group consisting of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN); the content of said at least one metal nitride selected from the group consisting of vanadium nitride (VN), niobium nitride (NbN) and hafnium nitride (HfN) is at least 10% by volume of the total binder phase, and the content of said at least one metal oxide is at least 10% by volume of the total binder phase; A polycrystalline cubic boron nitride sintered body, characterized in that
2. 10. The PCBN body of claim 1, wherein the binder phase further comprises at least one metal oxynitride that is a reaction product of one of the at least one metal oxide and one of the at least one metal nitride.
3. 3. The PCBN body of claim 2, wherein the binder phase comprises at least one oxynitride selected from the group consisting of zirconium oxynitride (Zr(O,N)), zirconium vanadium oxynitride ((Zr,V)ON), zirconium niobium oxynitride ((Zr,Nb)ON), and zirconium hafnium oxynitride ((Zr,Hf)ON).
4. 4. The PCBN body of claim 2 or 3, wherein the binder phase comprises at least one oxynitride selected from the group consisting of aluminum oxynitride (Al(O,N)), aluminum vanadium oxynitride ((Al,V)ON), aluminum niobium oxynitride ((Al,Nb)ON), and aluminum hafnium oxynitride ((Al,Hf)ON).
5. The binder phase is ZrO 2 , Al 2 O 3 10. The PCBN body of claim 1, comprising at least one metal nitride selected from the group consisting of AlN, VN, NbN and HfN.
6. 3. The PCBN body of claim 1 or 2, wherein a metal nitride selected from the group consisting of VN, NbN and HfN comprises up to 50 volume percent of the total binder phase.
7. The binder phase is ZrO 2 , Al 2 O 3 3. The PCBN body of claim 1 or 2, comprising at least one metal nitride selected from the group consisting of: AlN, VN, NbN and HfN, and at least one oxynitride selected from the group consisting of Zr(O,N), (Zr,V)ON, (Zr,Nb)ON, (Zr,Hf)ON, Al(O,N), (Al,V)ON, (Al,Nb)ON and (Al,Hf)ON.
8. 8. The PCBN body of claim 7, wherein the oxynitrides and metal nitrides selected from the group consisting of VN, NbN and HfN are between 10 and 50 volume percent of the total binder phase of the PCBN body.
9. ZrO 2 2. The PCBN body of claim 1, wherein is between 20 and 90 volume percent of the total metal oxide content of the binder phase.
10. A 2 O 3 3. The PCBN body of claim 1 or 2, wherein is between 5% and 25% by volume of the binder phase.
11. 3. A PCBN body according to claim 1 or 2, wherein the PCBN body (1, 2) is backed by a substrate (4) of cemented carbide.
12. 3. The PCBN body of claim 1 or 2, wherein the PCBN body is coated with a PVD or CVD coating having a thickness between 0.8 μm and 15 μm.
13. 3. A PCBN body according to claim 1 or 2, wherein the PCBN body (1, 2) is a cutting tool (3) or a cutting tip (2) of a cutting tool.
14. A method for producing a PCBN body (1, 2) according to claim 1 or 2, comprising the steps of: (a) providing cubic boron nitride (cBN) powder having an average particle size between 0.5 μm and 15 μm; (b) ZrO 2 , or ZrO 2 and Al 2 O 3 providing a binder composition comprising a mixture of at least one metal nitride selected from the group consisting of VN, NbN and HfN constituting at least 10 volume percent of the binder mixture, and metallic aluminum; (c) combining the binder composition with the cBN powder to form a powder mixture; (d) grinding the powder mixture; (e) forming a green body of the powder mixture; (f) heat treating the green body at a temperature above 600° C. under reduced pressure to ensure sufficient outgassing and removal of absorbed species; (g) sintering the green body at a temperature of at least 1200° C. and at a pressure of at least 4 GPa to form a solid PCBN body, thereby forming the PCBN body (1, 2); A manufacturing method comprising:
15. 3. Use of a PCBN body according to claim 1 or 2 for machining nickel-based and / or cobalt-based superalloys.